Noise-free recovery of optodigital encrypted and multiplexed images - Henao, Rodrigo (2010)
We present a method that allows storing multiple encrypted data using digital holography and a joint transform correlator architecture with a controllable angle reference wave. In this method, the information is multiplexed by using a key and a different reference wave angle for each object. In the recovering process, the use of different reference wave angles prevents noise produced by the nonrecovered objects from being superimposed on the recovered object; moreover, the position of the recovered object in the exit plane can be fully controlled. We present the theoretical analysis and the experimental results that show the potential and applicability of the method.